If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1d + c = z Reorder the terms: c + -1d = z Solving c + -1d = z Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add 'd' to each side of the equation. c + -1d + d = d + z Combine like terms: -1d + d = 0 c + 0 = d + z c = d + z Simplifying c = d + z
| 1/5=50/x | | 2.5x+0.5x=13.5+4.5x | | -204+(-4n)=-784 | | 2x+9y=26 | | 80/4=5 | | 0.10(h+5.00)=2.40 | | -5-2x=8x+3(x+2) | | 8=4*d | | 8+6x=30+2 | | -(3x-14)+2(4x+4)= | | 0.2x-2.8=4.6x+1.5 | | x-8/3+3x-24/3 | | 0.10(h+5.00)=2.00 | | -7a+9=3a | | 56mn^5+48m^8n^2+32m^2n^2= | | 6w^2+3w+5=0 | | -3.8-38.1524=1.8-5.2(7.8+2.4x) | | 1(y)=1(x+7) | | 4x+35=x-10 | | 54=5+4x | | 7(4+m)=whatism | | 15x+5=10-5 | | -8n+3n=-6-2n | | 2b-4=8b+1 | | 2a-b=c | | 14-S=96 | | y/10+404=427 | | X^2+4x+15=175 | | -1/2(2y+9) | | 3b-4-10b-7= | | 1400*5/3=x | | x+2+x+2+x+2+x+2+x+2= |